2019
DOI: 10.12938/bmfh.18-020
|View full text |Cite|
|
Sign up to set email alerts
|

Alleviation of low-fiber diet-induced constipation by probiotic <i>Bifidobacterium bifidum</i> G9-1 is based on correction of gut microbiota dysbiosis

Abstract: Constipation, a functional disorder of the digestive system, is common in children and adults and may compromise patient quality of life. Because many patients are not satisfied with the efficacy of existing therapies, in this study, we investigated the efficacy of the probiotic Bifidobacterium bifidum G9-1 (BBG9-1) in constipation induced by a low-fiber diet. After inducing constipation in rats by feeding a low-fiber diet, rats were fed a low-fiber diet mixed with BBG9-1 in 14 days to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 20 publications
(20 reference statements)
3
9
0
Order By: Relevance
“…A prior study has shown that G9-1 improves gut dysbiosis and increases the levels of butyrate-producing bacteria in the intestine. 51 Butyrate levels were also increased by G9-1 in our study; we suspect that this is due to changes in the gut microbiota composition. There were no significant differences between the ASA+PPI and the ASA+PPI+G9-1 groups.…”
Section: Discussionsupporting
confidence: 54%
“…A prior study has shown that G9-1 improves gut dysbiosis and increases the levels of butyrate-producing bacteria in the intestine. 51 Butyrate levels were also increased by G9-1 in our study; we suspect that this is due to changes in the gut microbiota composition. There were no significant differences between the ASA+PPI and the ASA+PPI+G9-1 groups.…”
Section: Discussionsupporting
confidence: 54%
“…BBG9-1 was reported to increase the amount of butyric acid in the intestine by improving the intestinal microbiota. 6 In this study, composition analysis at the family level showed a tendency for an increase of Lachnospiraceae (to which butyric acid-producing bacteria belong) in the BBG9-1 group, compared with that in the normal group; it was increased even with respect to that in the PHA group (Figure 2c). This suggested that the level of butyric acid in the intestines might be elevated in the BBG9-1 group.…”
Section: Effect Of Bbg9-1 On Villus Length Of Jejunumsupporting
confidence: 51%
“…The improvement in intestinal villus length, brought about by BBG9‐1, is also considered to be related to its effect on suppressing the hyperproliferation of E. coli . BBG9‐1 was reported to increase the amount of butyric acid in the intestine by improving the intestinal microbiota . In this study, composition analysis at the family level showed a tendency for an increase of Lachnospiraceae (to which butyric acid‐producing bacteria belong) in the BBG9‐1 group, compared with that in the normal group; it was increased even with respect to that in the PHA group (Figure c).…”
Section: Discussionmentioning
confidence: 99%
“…These interactions are mediated by the neural, endocrine, and immune systems to maintain intestinal homeostasis [2]; however, homeostatic dysfunction can significantly affect host immunity and the course of chronic inflammation [3]. Some probiotics and polysaccharides have been found to regulate intestinal and immune homeostasis; for instance, probiotic Bifidobacterium bifidum alleviates dysbiosis and constipation in mice induced by a low-fiber diet [4], while grains fermented with Aspergillus oryzae can protect against chronic constipation and gastrointestinal damage [5,6]. In addition, the soluble dietary fiber β-1,3-glucan from seaweed has been shown to suppress intestinal inflammation in mouse models of human inflammatory bowel disease by increasing the Lactobacillus population and the number of regulatory T cells in the colon [7].…”
Section: Introductionmentioning
confidence: 99%